Phytochemical Potential and Inhibitory Properties of New Varieties of Leguminous Plants - Veber A.; Leonova S.; Davletov F. (Техника и технология пищевых производств)
New varieties of leguminous plants expand the range and improve the quality of healthy food products. The new legumes meet the requirements of modern food production. In addition, they demonstrate low inhibitory properties and possess a high phytochemical potential. Domestic non-GM peas and beans have a high nutritional and biological value; they are cheap, highly profitable, and can be produced in large volumes. Thus, they have a high potential for expanding the raw material base of the food industry. The Republic of Bashkortostan is the leader in pea production: the State Register of Breeding Achievements contains over 10 varieties cultivated by Bashkir scientists. Researchers of the Omsk State Agrarian University have created high-yielding varieties of beans with improved consumer qualities that are adapted to Siberian environment. However, the qualitative indicators of the new varieties remain understudied. The present research expands the raw material base for the production of healthy and functional foods with the new legumes adapted to the conditions of West Siberia and the Urals. The study features the characteristics of legumes of Siberian and Ural ecotype, which helps to expand the information database on the phytochemical potential of the new varieties. The beans were provided by the Omsk State Agrarian University, the peas – by the Bashkir Research Institute of Agriculture (harvest of 2018). The main objectives of the study were to determine the indicators that form the nutritional and biological value of the raw materials: protein content, dietary fiber, the presence and quantity of macro and microelements, enzymes, and trypsin inhibitor, also during germination.